Dinamika Perkembangan Aliran Kepercayaan Di Kecamatan Pudak Kabupaten Ponorogo - Rochmad Rochmad; Muhammad Nurrosyid Huda Setiawan; Faisal Reza Pradhana; Syamsul Hadi Untung (Universitas Darussalam Gontor, 2021)
Pudak Subdistrict, Ponorogo Regency, East Java, is a fertile place for the growth of the group of believers. However, currently, the existence of these groups in Pudak is decreasing drastically, even though these groups have many positive teachings to strengthen the character of the Indonesian nation. This research, which uses a sociological approach, shows that there are only three groups of believers left in Pudak District, Ponorogo Regency, namely the Purwa Ayu Mardi Utama, Ilmu Sejati and Perjalanan. They spread across four villages, including Pudak Kulon, Pudak Wetan, Bareng and Banjarjo. Only the Purwa Ayu still has many followers, while the other two groups are almost extinct. One of the factors is that the Purwa Ayu association consistently socializes to the community. On the other hand, there is still discrimination against followers of the group of believers in Pudak Ponorogo, so that their followers often hide their identities. This Discrimination certainly hinders the development of the groups of believers.